1999
DOI: 10.1038/sj.bmt.1701936
|View full text |Cite
|
Sign up to set email alerts
|

Salvage therapy for refractory chronic graft-versus-host disease with mycophenolate mofetil and tacrolimus

Abstract: Summary:Chronic graft-versus-host disease (GVHD) is a common late complication of allogeneic bone marrow transplantation (BMT) and is the principal cause of morbidity and non-relapse mortality. The improved management of acute GVHD has not translated into lower rates of chronic GVHD as older patients undergo allogeneic BMT, more patients receive unrelated or related mismatched allogeneic BMT, and donor lymphocyte infusion is increasingly used for treatment of post-BMT relapses. Patients with high risk chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
2
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 12 publications
2
65
2
2
Order By: Relevance
“…Although not officially licensed, many investigators have used the compound to treat acute and chronic GVHD. 20,21 In addition, MMF was shown to be synergistic with CYA in inducing a stable mixed chimerism after nonmyeloablative conditioning in a large animal model and in subsequent clinical studies. 22,23 Studies on the use of MMF as part of GVHD prophylaxis have been limited in size and mostly inconclusive, as most investigators reported insufficient plasma levels of the active metabolite MPA.…”
Section: Discussionmentioning
confidence: 99%
“…Although not officially licensed, many investigators have used the compound to treat acute and chronic GVHD. 20,21 In addition, MMF was shown to be synergistic with CYA in inducing a stable mixed chimerism after nonmyeloablative conditioning in a large animal model and in subsequent clinical studies. 22,23 Studies on the use of MMF as part of GVHD prophylaxis have been limited in size and mostly inconclusive, as most investigators reported insufficient plasma levels of the active metabolite MPA.…”
Section: Discussionmentioning
confidence: 99%
“…This drug is commonly used for prophylaxis of acute GVHD, in combination with a calcineurin inhibitor, both after cord blood transplantation and reduced intensity regimens (Parikh et al, 2009;Sabry et al, 2009). Single-arm retrospective studies have shown some benefit in terms of improvement of symptoms and steroid reduction in patients receiving MMF as second-line therapy in chronic GVHD (Mookerjee et al, 1999;Lopez et al, 2005). Interestingly, in a double-blind placebo controlled study, when MMF was added to standard therapy to newlydiagnosed patients with chronic GVHD, there was no evidence of benefit from adding MMF .…”
Section: Mycophenolate Mofetil (Mmf)mentioning
confidence: 99%
“…18 This immunosuppressive agent might also be useful in the treatment of auto-immune diseases, such as diffuse proliferative lupus nephritis, in combination with prednisolone. 19 Preliminary clinical studies suggest that MMF might be an effective agent for prophylaxis of aGVHD 1,20,21 and/or treatment of acute 22,23 or chronic 14,22 GVHD after allogeneic BMT or PBSCT in adult patients or in children, 24 when administered alone or in combination with other immunosuppressive agents (CsA Ϯ prednisolone, 21,22 tacrolimus 14 ). However, few data are available.…”
mentioning
confidence: 99%
“…In the largest series of patients reported by Basara et al, 22 MMF was administered in combination with CsA and prednisolone in 30 patients with acute (21 patients) or chronic (9 patients) GVHD; overall grade improvement of aGVHD was found in 71% of patients and MMF therapy led to moderate improvment in 50% of patients with limited cGVHD. Used as a salvage therapy for refractory GVHD, MMF induced 46% objective response in a series of 26 adult patients, 14 while an overall response rate of 60% (complete and partial response) has been reported in a series of 15 children. 24 The bioavailability of the oral formulation of MMF, especially in patients with GVHD of the bowel, might be an important factor influencing the efficacy of MMF and the use of an i.v.…”
mentioning
confidence: 99%
See 1 more Smart Citation